Article Review: Implementation of Criminal Sanctions For Narcotic and Psychotropic Substance Abuse in Indonesia - Putri Ulan Sari; Rasmi Zakiah Oktarlina (Fox Justi : Jurnal Ilmu Hukum, 2025)
The abuse of narcotics and psychotropic substances is a serious issue with far-reaching impacts on public health, social stability, and national resilience. Although these substances have legitimate benefits in the fields of medicine and science, their illegal use poses significant risks to society, particularly to the younger generation. Indonesia has established criminal sanctions for perpetrators of drug abuse through Law Number 35 of 2009 on Narcotics and Law Number 5 of 1997 on Psychotropics. This study aims to analyze the application of criminal sanctions for the abuse of narcotics and psychotropics, including legal aspects, involvement of both the general public and medical personnel, and the effectiveness of the current law enforcement system. The findings indicate that the implementation of criminal sanctions still faces several challenges, such as inconsistencies in legal treatment, limited rehabilitation facilities, and weak control over drug distribution. Therefore, a more humane and integrated legal approach through prevention, treatment, rehabilitation, and repressive measures is crucial to breaking the cycle of drug abuse in Indonesia.